ANCA-associated vasculitis is linked to carriage of the Z allele of α1 antitrypsin and its polymers. Issue 10 (5th August 2011) - Morris, H; Morgan, M D; Wood, A M; Smith, S W; Ekeowa, U I; Herrmann, K; Holle, J U; Guillevin, L; Lomas, D A; Perez, J; Pusey, C D; Salama, A D; et al.
Abstract : Background: Small studies have linked α1 antitrypsin (α1AT) deficiency to patients with antineutrophil cytoplasmic antibodies (ANCA)-associated vasculitis (AAV). Objective: To test the validity and the mechanism of this association between α1AT and AAV. Methods: The distribution of α1AT deficiency alleles Z and S was compared between 856 White Europeans with AAV and 1505 geographic and ethnically matched healthy controls. Genotyping was performed by allelic discrimination assay. Results were compared between cases and controls using χ 2 tests. The serum and renal biopsies for α1AT polymers were compared using the polymer-specific 2C1 antibody. The role of α1AT polymers in promoting inflammation was investigated by examining their ability to prime neutrophils for ANCA activation as assessed by CD62L shedding, superoxide production and myeloperoxidase degranulation. Results: The Z but not the S allele was over-represented in the patients compared with controls (HR=2.25, 95% CI 1.60 to 3.19). Higher concentrations of polymers of α1AT were detected in serum from patients carrying the Z allele than in those not carrying the Z allele (median (IQR) 1.40 (0.91–3.32) mg/dl vs 0.17 (0.06–0.28) mg/dl, p<0.001); polymers of α1AT were also seen in the renal biopsy of a patient with vasculitic glomerulonephritis. Polymers of α1AT primed neutrophils with CD62L shedding and increased superoxide production following ANCA activation. Carriage of the Z allele was not associated with disease severity, survival or relapse. Conclusions: The Z but not the S deficiency allele is associated with AAV. Polymers of α1AT are present in the serum and glomeruli of at least some patients with the Z allele, which may promote inflammation through priming of neutrophils.